Dscam1 Is Required for Normal Dendrite Growth and Branching But Not for Dendritic Spacing in Drosophila Motoneurons - Hutchinson, Katie M. (Society for Neuroscience, 2014)
Down syndrome cell adhesion molecule, Dscam, serves diverse neurodevelopmental functions, including axon guidance and synaptic adhesion, as well as self-recognition and self-avoidance, depending on the neuron type, brain region, or species under investigation. In Drosophila, the extensive molecular diversity that results from alternative splicing of Dscam1 into >38,000 isoforms provides neurons with a unique molecular code for self-recognition in the nervous system. Each neuron produces only a small subset of Dscam1 isoforms, and distinct Dscam1 isoforms mediate homophilic interactions, which in turn, result in repulsion and even spacing of self-processes, while allowing contact with neighboring cells. While these mechanisms have been shown to underlie mushroom body development and spacing of mechanosensory neuron dendrites, here we report that Dscam1 plays no role in adult Drosophila motoneuron dendrite spacing, but is required for motoneuron dendritic growth. Targeted expression of Dscam-RNAi in an identified flight motoneuron did not impact dendrite spacing, but instead produced overgrowth. Increasing the knockdown strength severely reduced dendritic growth and branching. Similarly, Dscam mutant motoneurons in an otherwise control background (MARCM) were completely devoid of mature dendrites. These data suggest that Dscam1 is required cell autonomously for normal adult motoneuron dendrite growth in Drosophila. This demonstrates a previously unreported role of Drosophila Dscam1 in central neuron development, and expands the current understanding that Dscam1 operates as a cell adhesion molecule that mediates homophilic repulsion.